Beyond the zulu principle extraordinary profits from growth shares - Slater, Jim
From this book, readers will learn when to buy shares and, even more importantly, when to sell. Other aspects of investment are covered - such as creative accounting, portfolio management, overseas markets and the investor's relationship with their broker. This book is designed to help readers make extraordinary profits from ordinary shares.